1994
DOI: 10.1161/01.cir.89.3.1041
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of left ventricular mass in a population sample aged 36 to 37 years. Focus on lifestyle and salt intake.

Abstract: Background Echocardiographically determined left ventricular (LV) mass predicts adverse cardiovascular events in the general population. We have assessed the correlates of LV mass in a population-based study focusing on lifestyle and salt intake.Methods and Results A random sample of 120 persons born in 1954 was invited; 93 (42 men) entered the study. The subjects' physical activity and alcohol, tobacco, and coffee consumption were quantified by 2-month diary follow-up, and sodium intake was quantified by 7-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
11

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 46 publications
5
65
0
11
Order By: Relevance
“…Moreover, several studies reported a good correlation between stroke volume and LVM. [61][62][63][64][65] The data of this study do not permit separation of the direct contribution of leptin deficiency from mechanical effects of obesity on the LVM. As leptin/fat mass ratio correlated with the FFM, the influence of each of these variables cannot be isolated.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, several studies reported a good correlation between stroke volume and LVM. [61][62][63][64][65] The data of this study do not permit separation of the direct contribution of leptin deficiency from mechanical effects of obesity on the LVM. As leptin/fat mass ratio correlated with the FFM, the influence of each of these variables cannot be isolated.…”
Section: Discussionmentioning
confidence: 68%
“…In patients with hypertension, a close relation between high sodium intake and the presence of LVH has been shown in several crosssectional studies (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 85%
“…We also tested for heterogeneity of genotype distributions across ethnicities by the 2 test (3 d.f.). In both single-SNP and haplotype-based analyses, conditional multivariable logistic regression models were employed to estimate the odds ratios (ORs) (95% CI) for each genetic variant of type 2 diabetes risk with adjustments for multiple confounding variables including matching factors (age, clinical center, time of blood draw, and ethnicity), BMI, ln(fasting glucose), ln(fasting insulin), cigarette smoking (never, past, and current), alcohol intake (never, past, and current), postmenopausal hormone therapy (never, past, and current), type 2 diabetes family history (presence/absence), and total MET value (the energy expended by a person at rest; 1 MET ϭ 1 kcal ⅐ kg Ϫ1 body weight ⅐ h Ϫ1 [23]) from recreational physical activity per week at baseline. In single-SNP analyses, each SNP was coded as additive, dominant, and reces- …”
Section: Methodsmentioning
confidence: 99%